2013
DOI: 10.1103/physreva.88.013802
|View full text |Cite
|
Sign up to set email alerts
|

Stable single-wavelength emission from fully chaotic microcavity lasers

Abstract: We experimentally and numerically show that single-wavelength emission can be stably observed for a fully chaotic microcavity laser with a stadium shape under continuous wave condition. The emission pattern is asymmetric with respect to the symmetry axes of the laser cavity, and it cannot be explained by a single cavity mode. On the basis of numerical analysis, we interpret such a lasing as the result of frequency-locking interaction among several low-loss cavity modes. Moreover, we experimentally investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 38 publications
2
27
1
Order By: Relevance
“…To gain an insight into the computational capability of the microcavity-based RC, the numerical simulation was performed by using the Maxwell-Bloch (MB) model, where the gain medium is modeled as a simple two-level system [26]. Whereas the MB model is a simple model of microcavity lasers, the dynamical lasing phenomena can qualitatively be examined [27,28]. We assumed that the cavity is two-dimensionally extended on a plane, and the electric field is polarized perpendicular to the plane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain an insight into the computational capability of the microcavity-based RC, the numerical simulation was performed by using the Maxwell-Bloch (MB) model, where the gain medium is modeled as a simple two-level system [26]. Whereas the MB model is a simple model of microcavity lasers, the dynamical lasing phenomena can qualitatively be examined [27,28]. We assumed that the cavity is two-dimensionally extended on a plane, and the electric field is polarized perpendicular to the plane.…”
Section: Resultsmentioning
confidence: 99%
“…However, we remark that the results presented in this paper do not essentially depends on the cavity size in the normalized form; thus, the real values in actual experiments can be estimated. For example, when L = 100µm, average mode interval ∆ω i /(2π) will be of the order of gigahertz [28]. The photon lifetime τ c in the stadium cavity (without the waveguide) is estimated as 28 ps, and it can be changed by the amplification due to the gain medium.…”
Section: Estimation Of Parameter Values Toward Actual Experimentsmentioning
confidence: 99%
“…where ∆ i represents the lasing oscillation frequency. Note that the lasing mode i depends on the pumping power and can be a fusion of several modes that coalesce by frequency-locking, and separate into individual lasing modes with different frequencies as the pumping power decreases [10,20]. U i is supposed to be normalized.…”
Section: Dynamics Of Almost Stationary Lasing Statesmentioning
confidence: 99%
“…A recent experimental study of semiconductor 2D microcavity lasers has demonstrated that single-mode lasing is achieved with a stadium-shaped (i.e., fully chaotic) cavity, while multimode lasing with an elliptic (i.e., nonchaotic) cavity [10,11]. This drastic difference was at-tributed to the difference of spatial modal patterns between the stadium and elliptic cavities.…”
Section: Introductionmentioning
confidence: 99%
“…7 (d) for the device with r 0 = 50 µm, where the pumping currents were 90 mA in both cases. For chaotic cavity lasers, single-mode lasing has been experimentally observed with CW pumping [25][26][27][28]. For chaotic cavity lasers, it has been numerically observed that nonlinear interactions among modes reduce the number of lasing modes [29], and experimentally observed single-mode lasing is attributed to large modal overlaps between resonant modes [28].…”
Section: Sitymentioning
confidence: 99%